General aspects of infections by bacteria of the genus Salmonella, a public and animal health problem (Research, Society and Development, 2021)
Objective: The objective of the study was to highlight the general characteristics of Salmonella spp. as to pathophysiology, focusing on forms of control and correlating hygiene with food security. Methodology: a search was performed in the bibliographic databases: Science Direct, Google academic, Pubmed and Scielo, to select articles published between the years 2011-2020. The terms used were: Food infections, Salmonella spp., food safety, chicken meat, associated with each other in Portuguese and English. Results: The infectious process by Salmonella spp. it is complex, the bacterium is capable of producing more than 400 proteins that cause inflammatory reactions, even if they are not hosted inside the intestinal cell and depending on its serotype it can cause various diseases, such as gastroenteritis and typhoid fever. Conclusion: In view of the above, it is possible to conclude that Salmonella spp. is among the main agents involved in food toxinfections, is commonly isolated in foods of poultry origin (as well as foods made from eggs) and swine, this transmission is also caused lack of hygiene on the part of handlers, as well as the improper storage of products and consumption of fresh or undercooked food.